2021
DOI: 10.2196/24405
|View full text |Cite
|
Sign up to set email alerts
|

Using Electronic Medical Record Data for Research in a Healthcare Information and Management Systems Society (HIMSS) Analytics Electronic Medical Record Adoption Model (EMRAM) Stage 7 Hospital in Beijing: Cross-sectional Study

Abstract: Background With the proliferation of electronic medical record (EMR) systems, there is an increasing interest in utilizing EMR data for medical research; yet, there is no quantitative research on EMR data utilization for medical research purposes in China. Objective This study aimed to understand how and to what extent EMR data are utilized for medical research purposes in a Healthcare Information and Management Systems Society (HIMSS) Analytics Electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…EMR, which is an online version of patient & population health information is a vital data source for HI. EMR helps in catering the relevant clinical information and in evaluating the diagnostic process (Li et al, 2021). Eventually, an EMR provides real-time scores that help in transferring intensive care to the patients in hospital mortality check (Escobar et al, 2016), risk of readmission, length of stay for maximum days, and discharge diagnosis (Rajkomar et al, 2018).…”
Section: Electronic Medical Records (Emr)mentioning
confidence: 99%
“…EMR, which is an online version of patient & population health information is a vital data source for HI. EMR helps in catering the relevant clinical information and in evaluating the diagnostic process (Li et al, 2021). Eventually, an EMR provides real-time scores that help in transferring intensive care to the patients in hospital mortality check (Escobar et al, 2016), risk of readmission, length of stay for maximum days, and discharge diagnosis (Rajkomar et al, 2018).…”
Section: Electronic Medical Records (Emr)mentioning
confidence: 99%
“…Beyond facilitating telemedicine, there is a sizable body of literature on the impacts, mostly beneficial, of EMR transitions on physician use, patient experience, and hospital efficiency [6][7][8][9][10]. EMRs are key data management tools as well as important validation tools for reducing clinician error [11].…”
Section: Expansion Of Electronic Medical Recordsmentioning
confidence: 99%
“…Meta-analyses [ 15 - 18 ] have found that big data platforms in health care have had great impacts on have had great impacts on medical technology, medical service quality, and medical costs, but the actual construction process is not easy, with challenges arising in data structurization, security, standardization, storage, processing, and management [ 15 , 16 ]. As a result, the value mined from this type of data is currently limited [ 17 ], and in China, health care data utilization is still in the early stage [ 18 ], which necessitates the improvement of health care big data governance.…”
Section: Introductionmentioning
confidence: 99%